Avaliação de um ciclo de rotação cultural milho e feijão-de-corda, utilizando-se água de baixa e de alta salinidade. - Sousa, Geocleber Gomes de (2008)
Aiming to assess the effects of salinity in the chemical characteristics of the soil, growth, partition of dry matter and productivity, and the effects of soil salinity on the levels mineral elements contend and the total extracted Na, macronutrients (Ca, K, Mg, P) and micronutrients (Cl, Fe, Cu, Zn and Mn), according to the salinity of the water irrigation, an experiment was carried out in the field according with randomized block design, with four treatments (T1, T2, T3 and T4) and five repetitions. In the cropping rotation was planted the maize in the spacing between lines of 0.8 m and 0.2 m between plants irrigated with water from high salinity and cowpea in the spacing between lines of 0.8 m and 0.3 m between plants irrigated with water with low salinity. The treatments used in the dry season maize crop in were: T1 (plants irrigated with water with low salinity), T2 (saline water with ECw of 2.2 dS m-1); T3 (saline water with ECw of 3.6 dS m-1); T3 (saline water with ECw ds of 3.6 m-1) and T4 (saline water with ECw of 5.0 dS m-1). For cropping of cowpea in the rainy season the plots were demarcated. During the rotation croppoing were assessed the following characteristics: chemical characteristics of soil, vegetation growth, partition of dry and productivity. They were also evaluated the levels of elements and minerals extracted from the total nutrients in the corn crop at 90 days after sowing. The application of saline waters caused increased salinity and sodicity soil during the dry period, and rainfall in the rainy season have been effective in washing the excess salts in the soil profile,increasing salinity of irrigation water above 2,2 dS m-1 reduced the vegetative growth, productivity and rate of harvest of maize, the accumulation of salts in the soil for the cultivation of maize in the dry season did not affect the productivity of cowpea, which was due to the high volume of rain that occurred just before and after the cultivation, this excess of rain, however, caused an no normal growth of cowpea with predominance vegetative of shares to the detriment of the production of grains. The levels of mineral elements varied in the maize crop to 90 days after the planting, being affected by salinity of irrigation water, as the higher the level of salinity irrigation water to 90 days after sowing as lower the levels of potassium in the leaves, magnesium and phosphorus in grains, and the plants of maize under low salinity irrigation water, extract nurtrient in the following order: K> Mg> Cl> Ca> P> Na> Fe> Zn> Mn> Cu however under salinity estress the maize crop extract the minerals to higher salinity level in the following order: K> Cl> Ca> Na> P> Mg> Mn> Zn> Cu and the salt decreases the extraction total the following minerals: K, Ca, Mg e P. The salinity has the following distribution of mineral elements: Na and K remained in the vegetative parts, Ca, Mg and P was exported in larger proportions to the reproductive organs, Cl, Mn and Cu were mainly in the vegetative parts, Fe and Zn was exported in larger proportions by grain.